Answer:
10
Step-by-step explanation:
say x=0
then y would be 1
increasing x by 5 makes x=5
and then 5 x 2 + 1=11
so y went from 1-11(difference of 10) with the variation
so the answer is 10
Answer:
the right answer is a) 23
Step-by-step explanation:
because when we analyze the sequence it is observed that all the numbers are added the value of 3, therefore when arriving at position 10 the sum is 23
594 divides by 34 equals 17.47
Answer:
hi
Step-by-step explanation:
Sorry u gonna fail cause I to dumb.
Answer:
-13
Step-by-step explanation:
hello,
Replace x by the value as below
![g(3)=3^2-4\times3=9-12=-3\\f(g(3))=f(-3)=4\times(-3)-1=-12-1=-13\\](https://tex.z-dn.net/?f=g%283%29%3D3%5E2-4%5Ctimes3%3D9-12%3D-3%5C%5Cf%28g%283%29%29%3Df%28-3%29%3D4%5Ctimes%28-3%29-1%3D-12-1%3D-13%5C%5C)
Thanks